The Monetary Transmission Mechanism in Jordan - Poddar, Tushar (IMF Working Papers; Working Paper, 2006)
This paper examines monetary transmission in Jordan using the vector autoregressive approach. We find that the real 3-month CD rate, the Central Bank's operating target, affects bank retail rates and that monetary policy, measured by the spread between the 3-month CD rate and the U.S. Federal Funds rate, is effective in influencing foreign reserves. We do not find evidence of monetary policy affecting output. Output responds very little to changes in bank lending rates. Furthermore, equity prices and the exchange rate are not significant channels for transmitting monetary policy to economic activity. The effect of monetary policy on the stock market seems insignificant.